(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the theoretical foundations of using podcasts in English language teaching. The role of information and communication technologies in modern language education, the didactic potential of podcasts, and their importance in developing listening and speaking skills are highlighted. The article also examines the classification of podcasts, methods of working with them, and theoretical aspects of their integration into the educational process. The author summarizes the scientific views of foreign and domestic researchers on the use of podcasts.